EFEKTIFITAS MODEL THINK TALK WRITE DALAM PEMBELAJARAN MENULIS TEKS RESENSI - Septian Nur Wahyudin; Sri Lestari Alami; Rochmat Tri Sudrajat (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is motivated by the difficulty of students in producing a review text that has not reached the assessment criteria. This research problem is whether the Think Talk Write learning model is effectively used in learning to write text? So this study aims to determine the effectiveness of the Think Talk Write learning model in learning to write text. The subjects used as the research sample were class X students. The research method used was pre-experimental in the form of one group pretest-posttest. The instruments used included RPP and test sheets. The results of the study show that student learning outcomes have a significant increase. This is evidenced by the average pretest value of 60 increasing at the posttest average value to 80. The application of this learning model gets a good response from students, can train critical thinking skills, and improve students' writing skills. So, based on the results of these studies it can be concluded that the Tnink Talk Write learning model is effectively used in learning to write texts.